2019
DOI: 10.1063/1.5111716
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance and spin-torque effect in flexible nanoscale magnetic tunnel junction

Abstract: Flexible electronics or hybrid electronics exhibit great potential for widespread applications in future wearable electronics. In this work, we fabricated flexible nanoscale MgO-barrier magnetic tunnel junctions (MTJs) using a transfer printing process. The magnetic transport measurements reveal that the fabricated devices possess excellent performance with a tunnel magnetoresistance ratio of ∼130% under different strained conditions. In addition, we also studied the spin-torque diode effect under different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…[74] Moreover, flexible nanoscale MTJ with MgO-based barrier with TMR about 130% were fabricated using a transfer printing process recently. [75] It was found that the rectified voltage and resonant frequency of STD effect for this MTJ is similar to the ones observed in STD fabricated by standard techniques. This result suggests that the properties of STDs are quite resistant to mechanical stresses, which makes flexible microwave spintronics very promising for various applications.…”
Section: Std's Applicationssupporting
confidence: 73%
“…[74] Moreover, flexible nanoscale MTJ with MgO-based barrier with TMR about 130% were fabricated using a transfer printing process recently. [75] It was found that the rectified voltage and resonant frequency of STD effect for this MTJ is similar to the ones observed in STD fabricated by standard techniques. This result suggests that the properties of STDs are quite resistant to mechanical stresses, which makes flexible microwave spintronics very promising for various applications.…”
Section: Std's Applicationssupporting
confidence: 73%